Saturated Fatty Acid-Induced Endoplasmic Reticulum Stress and Insulin Resistance Are Prevented by Imoxin in C2C12 Myotubes - Eo, Hyeyoon; Valentine, Rudy J (Frontiers in Physiology, 2022)
In obesity, plasma free fatty acids (FFAs) levels are elevated due to enlarged adipose tissue mass. Saturated fatty acids can induce prolonged ER stress and insulin resistance. Double-stranded RNA-dependent Protein Kinase (PKR) is activated under stress conditions in skeletal muscle. The current study aimed to investigate the effect of imoxin (IMX), a selective PKR inhibitor, on palmitate (PA)-induced ER stress and insulin resistance in C2C12 myotubes. Cells were treated with 5 uM IMX and exposed to 0.5 mM bovine serum albumin (BSA)-conjugated PA for 24 hr. A subset of cells was stimulated with 50 nM insulin for the last 15 min. Glucose uptake was monitored and protein levels involved in ER stress and insulin signaling were measured by Western blotting. PA stimulated PKR phosphorylation, which was prevented by IMX. Moreover, IMX reduced protein levels of ER stress-related markers including glucose-regulating protein 78 (GRP78), CCAAT-enhancer-binding protein homologous protein (CHOP), activating transcription factor 6 (ATF6) and spliced X-box binding protein 1 (XBP-1s) which were induced by PA. Furthermore, IMX ameliorated PA-induced suppression of phospho-insulin receptor beta (p-IRβ) and Akt phosphorylation in myotubes. In addition, IMX promoted glucose uptake in response to insulin under PA exposure. Furthermore, IMX reduced phospho-c-Jun N-terminal kinase (p-JNK) induced by PA treatment. These findings suggest that IMX may protect against saturated fatty acid-induced ER stress and insulin resistance in skeletal muscle, which are potentially mediated by PKR.